Positive/retained SDHB immunostaining in renal cell carcinomas associated to germline SDHB-deficiency: case report - Marina Ugarte-Camara; Raul Fernandez-Prado; Isabel Lorda; Gabriela Rossello; Carmen Gonzalez-Enguita; Pablo Cannata-Ortiz; Alberto Ortiz (BMC, 2019)
Abstract Background According to WHO, succinate dehydrogenase (SDH)-deficient renal cell carcinoma is characterized by negative immunostaining for SDHB, which remains positive in non-tumor tissue despite germline mutations in the SDHB gene. We now report a patient with a SDHB mutation, c.166_170del (p.Pro56Tyrfs*5) who developed renal cell carcinomas with characteristic morphological features of SDH-deficient renal cell carcinoma but had positive SDHB immunostaining. Case presentation Within a 6-year period, the patient developed two different renal cell carcinomas, which had characteristic morphological features of SDH-deficient renal cell carcinoma (uniform cells characteristically displaying eosinophilic granular material intermixed with fewer cells exhibiting clear intracytoplasmic inclusions and bland centered nuclei) but displayed immunohistochemistry for SDHB with a cytoplasmic granular positivity (mitochondrial pattern) in tumor cells. For the second case, this was initially interpreted as positive by IHC, but on review some subtle differences were identified. Conclusions SDHB immunostaining may be positive in renal cell carcinoma associated to germline SDHB deficiency which have other typical morphological features. Immunohistochemistry interpretation may be complex.